2013
DOI: 10.3892/br.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of α-glucosidase inhibition by Cudrania tricuspidata according to harvesting time

Abstract: Abstract. Cudrania tricuspidata (CT) is a type of add-value beneficial plant. The aim of the present study was to determine the components of CT that inhibit α-glucosidase activity. Roots, leaves and stems of the plants were obtained and several subgroups were created according to harvesting time. Root extracts exhibited a 77% velocity inhibition at a concentration of 300 µg/ml and an inhibitory constant of 41.6 µg/ml. The inhibitory percentage of the positive control at 1 mM was ~67% of the enzymatic velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
3
11
1
Order By: Relevance
“…For SVPA, both enzymes were inhibited uncompetitively in the in vitro studies and non-competitively in the molecular docking analyses, while SEPA revealed a non-competitive inhibition in vitro and a competitive inhibition in the molecular docking against α-glucosidase. Also, acarbose, a known competitive inhibitor of αglucosidase was confirmed to exhibit competitive inhibition in the present study with molecular docking analysis but a number of in vitro experiments have also shown that acarbose is a mixed inhibitor [25,26]. These observations demonstrate the need to further validate some of the docking data with in vitro experiments.…”
Section: Discussionsupporting
confidence: 58%
“…For SVPA, both enzymes were inhibited uncompetitively in the in vitro studies and non-competitively in the molecular docking analyses, while SEPA revealed a non-competitive inhibition in vitro and a competitive inhibition in the molecular docking against α-glucosidase. Also, acarbose, a known competitive inhibitor of αglucosidase was confirmed to exhibit competitive inhibition in the present study with molecular docking analysis but a number of in vitro experiments have also shown that acarbose is a mixed inhibitor [25,26]. These observations demonstrate the need to further validate some of the docking data with in vitro experiments.…”
Section: Discussionsupporting
confidence: 58%
“…This suggests that peptides in AAIE1 can bind to both enzyme (E) and enzyme–substrate complex (ES), but with different affinities. Interestingly, the mode of action of AAIE1 was the same as that of Acarbose, which is one of the standard prescription drugs for the management diabetes (Son & Lee, ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that GAIE1 fraction can bind to both the enzyme and the enzyme–substrate complex but with different affinities. The mode of action of GAIE1 was essentially the same as that of acarbose, which also exhibits a mixed non‐competitive mode of action against α ‐glucosidase …”
Section: Resultsmentioning
confidence: 99%